Impact of Foundational Literacy and Numeracy Programme Among the Students Studying in Government Schools - Vishwakarma, Bhola; Pal, Sita Ram (JOURNAL OF INDIAN EDUCATION, 2026)
The Government of India has launched several flagship schemes and policies to strengthen the education system, with a strong focus on foundational literacy and numeracy (FLN). Key initiatives such as the National Education Policy (NEP) 2020 and the NIPUN Bharat Mission are aligned with the Sustainable Development Goals (SDG) 2030. Launched in July 2021, the NIPUN Bharat Mission aims to ensure that students in Grades 1 to 3 achieve foundational proficiency in language and mathematics by 2026–27. This study evaluates the progress of NIPUN Bharat in Varanasi district, covering 77,109 students across 1,009 government schools during the 2023–24 academic session. Assessments conducted between July and December 2023 indicate substantial improvements in foundational skills. Proficiency in Hindi increased from 25.11 per cent to 81.86 per cent, while mathematics proficiency rose from 27.61 per cent to 82.83 per cent. Overall NIPUN proficiency improved from 23.12 per cent in July to 80.35 per cent in December, 2023. Notably, the Sewapuri block recorded a 64.47 per cent increase, setting a benchmark for grassroots success. Comparisons between school-reported data and third-party assessments validated the accuracy of reporting. The programme’s holistic approach, combining data-driven strategies with innovative teaching practices, has fostered greater confidence and curiosity among students. The findings highlight the transformative impact of targeted interventions and demonstrate the replicable potential of the NIPUN Bharat Mission, for improving foundational learning outcomes nationwide.